Treatment with Antibiotics that Interfere with Peptidoglycan Biosynthesis Inhibits Chloroplast Division in the Desmid Closterium - Matsumoto, Hiroko (Public Library of Science, 2012)

(untitled)
Charophytes is a green algal group closely related to land plants. We investigated the effects of antibiotics that interfere with peptidoglycan biosynthesis on chloroplast division in the desmid Closterium peracerosum–strigosum–littorale complex. To detect cells just after division, we used colchicine, which inhibits Closterium cell elongation after division. Although normal Closterium cells had two chloroplasts before and after cell division, cells treated with ampicillin, D-cycloserine, or fosfomycin had only one chloroplast after cell division, suggesting that the cells divided without chloroplast division. The antibiotics bacitracin and vancomycin showed no obvious effect. Electron microscopic observation showed that irregular-shaped chloroplasts existed in ampicillin-treated Closterium cells. Because antibiotic treatments resulted in the appearance of long cells with irregular chloroplasts and cell death, we counted cell types in the culture. The results suggested that cells with one chloroplast appeared first and then a huge chloroplast was generated that inhibited cell division, causing elongation followed by cell death.